2017
DOI: 10.1116/1.5003375
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the atomic layer deposition temperature on the structural and electrical properties of Al/Al2O3/p-Ge MOS structures

Abstract: The influence of deposition temperature on the structural, chemical, and electrical properties of atomic layer deposition (ALD)-Al2O3 thin films is investigated. ALD-Al2O3 films were deposited on p-type Ge substrates at 80, 150, 200, 250, and 300 °C. The atomic force microscopy analysis reveals smooth and cohesive films with extremely low roughness (0.2–0.6) nm at 150, 200, 250, and 300 °C. On the contrary, Al2O3 films deposited at the lowest available deposition temperature (80 °C) exhibit holes and aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Two ultra-thin ZnO films of 0.6 and 1.0 nm were also prepared using four and six cycles respectively. The thickness of similar, up to 10 nm, films has been investigated by our team previously [29][30][31] and it was shown that the nominal growth rates are in agreement with the calculated ones. Also, films with thickness of at least 20 nm of Al 2 O 3 , ZrO 2 , HfO 2 and Ta 2 O 5 were prepared and will be noted as reference samples.…”
Section: Sample Preparationsupporting
confidence: 62%
“…Two ultra-thin ZnO films of 0.6 and 1.0 nm were also prepared using four and six cycles respectively. The thickness of similar, up to 10 nm, films has been investigated by our team previously [29][30][31] and it was shown that the nominal growth rates are in agreement with the calculated ones. Also, films with thickness of at least 20 nm of Al 2 O 3 , ZrO 2 , HfO 2 and Ta 2 O 5 were prepared and will be noted as reference samples.…”
Section: Sample Preparationsupporting
confidence: 62%
“…For example, we expect the 9.4 nm thick oxide layers to be above the electron tunneling length and therefore to be nonconductive, even with the present H doping content. [ 58 ] Hence, we would expect there to be a poorer conductivity for the 50/9.4 sample than the 50/1 cycle or 150 counterparts.…”
Section: Discussionmentioning
confidence: 99%